RE-AIM applied to a primary care workforce training for rural providers and nurses: the Department of Veterans Affairs' Rural Women's Health Mini-Residency - Golden, Rachel E.; Sanders, Aimee M.; Frayne, Susan M. (Frontiers in Health Services, 2023)
Abstract: Introduction: Application of the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework to evaluate workforce education and training programs targeting clinical health care staff has received relatively little attention. This paper aims to contribute to this area with RE-AIM findings from a women’s health-focused workforce training program implemented by the U.S. Department of Veterans Affairs (VA). Over the past two decades, the rapid expansion of the women Veteran population in VA has necessitated a rapid response to meet clinical demand. To address this health care need, the VA Offices of Rural Health (ORH) and Women’s Health (OWH) partnered to deploy a primary care workforce development initiative for Rural Providers and Nurses – the Rural Women’s Health Mini-Residency (Rural WH-MR) – to train VA clinicians in rural locations in skills for the care of women Veterans. Here we assess the applicability of RE-AIM as an evaluation framework in this context. Methods: We evaluated the Rural WH-MR, relying on a primarily quantitative approach, rooted in RE-AIM. It included longitudinal and cross-sectional measurements from multiple quantitative and qualitative data sources to develop selected metrics. Data collection instruments consisted of pre-, post-, and follow-up training surveys, course evaluations, existing VA databases, and implementation reports. We developed metrics for and assessed each RE-AIM component by combining data from multiple instruments and then triangulating findings. Results: Results from the Rural WH-MR program for fiscal years 2018-2020 indicate that RE-AIM provides an instructive evaluation framework for a rural workforce training program, particularly in eliciting clarity between measures of Reach versus Adoption and focusing attention on both provider- and patient-level outcomes. Discussion: We describe evaluation metric development and barriers to and facilitators of utilizing RE-AIM as an evaluation framework for a provider- and nurse-facing intervention such as this workforce training program. We also reflect upon RE-AIM benefits for highlighting process and outcomes indicators of a training program’s success and lessons learned for evaluating rural workforce development innovations. Several of our observations have implications for training and evaluation approaches in rural areas with more limited access to health care services.